Senior High School Students’ Higher Order Thinking Skills in Solving Combinatorics Problems - Arif Fatahillah; Vahad Agil Liyandri; Lioni Anka Monalisa (Jurnal Pendidikan Matematika, 2022)
Higher Order Thinking Skills (HOTS) refer to students' ability to solve problems by analyzing, evaluating, and creating. HOTS are essential for 21st century learning. Solving combinatorics problem troubleshooting requires HOTS. The aim of this research is to examine of senior high school students’ higher order thinking skills in solving combinatorics problems. This descriptive research describes the analysis of senior high school students’ higher order thinking skills in solving combinatorics problems. Class XII IPA 6 SMA Negeri 1 Trenggalek has a total of 21 students. Data was collected through a written test containing combinatorics problems and interviews. The results of the study show the senior high school students’ higher-order thinking skills in solving combinatorics problems: 38% of the students have "excellent" performance; 14% are rated as good; 10% are classified as enough; 38% are classified as low; no one is very poor. The most common indicator of higher-order thinking skills was analyzing (58%), followed by evaluating (55%). The creating rate is the lowest at 47%. This study can develop students' higher order thinking skills and evaluation for teachers in implementing higher order thinking skills in school.